Memoria social como elemento cohesionador de identidad comunitaria desde los pobladores de mayor estancia y de residencia en el barrio “Los Pinos” durante el año 2015 - Carrillo Martínez, Daniel Antonio (2016)
This research paper has the purpose to try to preserve what can be called a social memory, that would mean, the different psychic circumstances in which the human mind solves and files life experiences. It does this with the objective to give argument or reasoning to any social thought which might seem a paradigm model or as simply as a social scheme related to work or understanding. It is in this way that the social memory records different situations that happen in a determine social space, and because this situation continues in a long period of time it will créate a reality system. This system can become a reference for human beings to understand reality and as a way to project themselves in the future. For this reason, this research paper is an attempr to preserve and systematize this experience that happen in the neigborhood Los Pinos , located south of Quito. This social space emerged so that the population had the possibility to express their opinions , cuilt their reality and so try to reveal a reality from exclusion, marginalization, antagonism, and the building of communities and subjectivity. A situation that up to this day is still overlapping and maintained outside official records and has become the history of the excluded communities.